Carbon and nitrogen stable isotopes of well-preserved Middle Pleistocene bone collagen from Schöningen (Germany) and their paleoecological implications. Issue 89 (December 2015) - Kuitems, Margot; van der Plicht, Johannes; Drucker, Dorothée G.; Van Kolfschoten, Thijs; Palstra, Sanne W.L.; Bocherens, Hervé
Abstract: Carbon and nitrogen stable isotopes in bone collagen can provide valuable information about the diet and habitat of mammal species. However, bone collagen degrades in normal circumstances very rapidly, and isotope analyses are therefore usually restricted to fossil material with a Late Pleistocene or Holocene age. The Middle Pleistocene site of Schöningen, dated to around 300, 000 years ago, yielded bones and teeth with an exceptionally good state of collagen preservation. This allowed us to measure reliable biogenic carbon and nitrogen stable isotope ratios for different herbivorous taxa from the families Elephantidae, Rhinocerotidae, Equidae, Cervidae, and Bovidae. The results provide insights regarding the paleoenvironmental setting in which Middle Pleistocene hominins operated. The vegetation consumed by the herbivores from the famous spear horizon originates from open environments. During the climatic Reinsdorf Interglacial optimum, the landscape seems to have been relatively open as well, but certainly included parts that were forested. The results also indicate some niche partitioning; different herbivore species used different plant resources. For instance, the horses seem to have been predominantly browsers, while the straight-tusked elephants were feeding chiefly on grass.